Strategi Peningkatan Mutu Lembaga Pendidikan Madrasah - Zohriah, Anis; Bachtiar, Machdum; Nasrudin, Anas (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
The quality of education is the main goal that every madrasa wants to achieve. Quality is a must that must be achieved in order to increase public trust in madrasas. Because quality-oriented madrasahs will be the institutions of choice, this is because most madrasas, especially madrasahs managed by the community, have suffered setbacks. The quality of madrasah education services will be determined by the extent to which madrasahs can optimally manage all existing capabilities and resources, the paradigm that must be built by madrasahs is to build quality. This research method uses descriptive qualitative research methods dan the type of research used is the library research method . is a study based on the philosophy of postpositivism that uses interpretative and constructive paradigms. Quality management aims to improve the quality of work, increase productivity and efficiency by increasing performance and improving the quality of work. High-quality education is not only reflected in the quality of graduates but also in the quality of educational institutions that can meet and serve customer needs according to applicable quality standards. The central basic technique for continuous quality improvement is improving the quality of all objects processed in education administration, starting from teachers, students, curriculum, learning processes, educational institutions, financing, and also relations with the community. Madrasas that live mainly from, through, and for the community need attention and support from all parties. Quality improvement does not occur without input from all parties. Therefore, to improve their quality, madrasas must be assisted to maintain and struggle so that they can live and develop and compete with other educational institutions. Keywords: Concept of Quality, Quality of Education, Quality Strategy